PENGEMBANGAN ALAT PERAGA PAPAN KONVERSI SATUAN DALAM PEMBELAJARAN MATEMATIKA PADA KELAS IV SDN 03 KOTO BARU - Eka Filahanasari; Ahmad Ilham Asmaryadi; Dena Putri Wiyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study is motivated by problems in the implementation of the Mathematics learning process in class IV, namely the low interest in learning of students and the weak understanding of students in mathematics subjects. Efforts to overcome these problems are to develop unit conversion board props that can improve student learning outcomes with attractive learning media. This type of research uses the type of research and development R & D (Research and Development). The development model used is the ADDIE development model, namely: Analyze, what is done is to analyze learning in accordance with the needs of students. Design, determine the design of the unit conversion board that will be made according to the material that has been determined. Development, is an advanced stage of the analysis and design stages. Implementation, the results of development are applied in learning to determine effectiveness, attractiveness and practicality. Evaluation, is a process carried out to provide value to the learning outcomes that have been learned. The results of this research and development have produced teaching materials in the form of unit conversion board props in learning Mathematics in class IV obtained from 3 validators, the validity of the unit conversion board props obtained from 5 validation experts getting an average percentage of 84.14% categorized as very valid, the practicality of the unit conversion board props obtained from educators and students with an average percentage of 91.78% categorized as very practical, the results of the effectiveness carried out by 27 students following learning using the unit conversion board developed with an average of 92.60% categorized as very effective.